Hyperkinetic Movement Disorder Secondary to Punctate Hemorrhage in Lateral Ventricle Lining - Atif Zafar; Sahrish Abdin (Case Reports in Neurology, 2015)
We present the case of an elderly male with hyperkinetic movements of the right arm and leg due to a small hemorrhage in the lateral aspect of the left lateral ventricle atrium. As per our database search, this is a unique presentation of a stroke in this particular location.